Route of Infection Strongly Impacts the Host-Pathogen Relationship - Demars, Aurore; Lison, Aurore; Machelart, Arnaud; Van Vyve, Margaux; Potemberg, Georges; Vanderwinden, Jean-Marie; De Bolle, Xavier; Letesson, Jean-Jacques; Muraille, Eric (Frontiers in Immunology, 2019)
Live vaccines play a key role in the control of many human and animal pathogens. Their rational development is usually helped by identification of the reservoir of infection, the lymphoid subpopulations associated with protective immunity as well as the virulence genes involved in pathogen persistence. Here, we compared the course of Brucella melitensis infection in C57BL/6 mice infected via intraperitoneal (i.p.), intranasal (i.n.) and intradermal (i.d.) route and demonstrated that the route of infection strongly impacts all of these parameters. Following i.p. and i.n. infection, most infected cells observed in the spleen or lung were F4/80+ myeloid cells. In striking contrast, infected Ly6G+ neutrophils and CD140a+ fibroblasts were also observed in the skin after i.d. infection. The virB operon encoding for the type IV secretion system is considered essential to deflecting vacuolar trafficking in phagocytic cells and allows Brucella to multiply and persist. Unexpectedly, the virB Brucella strain, which does not persist in the lung after i.n. infection, persists longer in skin tissues than the wild strain after i.d. infection. While the CD4+ T cell-mediated Th1 response is indispensable to controlling the Brucella challenge in the i.p. model, it is dispensable for the control of Brucella in the i.d. and i.n. models. Similarly, B cells are indispensable in the i.p. and i.d. models but dispensable in the i.n. model. + T cells appear able to compensate for the absence of 𝛼𝛽+ T cells in the i.d. model but not in the other models. Taken together, our results demonstrate the crucial importance of the route of infection for the host pathogen relationship.